Une reine entre ombres et lumières ou le pouvoir au féminin : le cas d’Isabelle Bourbon, reine d’Espagne, première femme de Philippe IV (1603-1644) - Frédérique Sicard (Genre & Histoire)
The role of French queens and their relation to power were strictly regulated, but their political influence is difficult to assess given the shadows within which they worked. In 1615, Isabelle of Bourbon, born Princess of France, married Philip of Spain and became one of these seldom-studied Queens of the shadows. What illumination does Queen Isabelle’s case bring to the gender-power relationship during the Golden Age? Three points are addressed in the article: the tensions and power dynamics around Philip IV; the weight of the family, in a broad sense, which necessarily affected relations between gender and power. Finally, we will focus on the political activity of Queen Isabelle; her example constitutes a concrete example of women’s power in the Golden Age.